Optical Properties of Plasmonic Ultrathin TiN Films. Issue 13 (26th May 2017) - Shah, Deesha; Reddy, Harsha; Kinsey, Nathaniel; Shalaev, Vladimir M.; Boltasseva, Alexandra
Abstract : Overcoming the challenge of growing ultrathin metallic films is of great importance for practical applications of nanoplasmonic structures. In the present work, epitaxial, ultrathin (<10 nm) films of plasmonic TiN are grown on MgO using DC reactive magnetron sputtering. The optical properties of the films are studied through variable angle spectroscopic ellipsometry and Hall measurements. As the film thickness decreases, they become less metallic and exhibit higher loss while still remaining plasmonic in the optical range. These trends are related to the decreasing carrier concentration in the thinner films and increased scattering, respectively. However, all films tested (2, 4, 6, 8, and 10 nm) still remain highly metallic with a carrier concentration on the order of 10 22 cm −3 . Based on the relationship between the plasma frequency, carrier concentration, and effective mass, it is determined that the reduction in carrier concentration plays the main role in defining the film's optical properties, as variations in the effective mass are found to be minimal for thicknesses above 4 nm. However, for the 2 nm film and below, theoretical calculations begin to deviate from experimental values. Abstract : The optical properties of epitaxial, ultrathin films (<10 nm) of TiN are characterized by ellipsometry and Hall measurements. The decreasing metallicity and lower losses in thinner films is attributed to the increase in their defect concentration. However, even at 2 nm, the films exhibit a high carrier concentration, indicating that they remain plasmonic.